Effectiveness of BEGESAH (Berbagai Edukasi Gerakan Masyarakat Sehat) Based on Local Wisdom on Awareness in Stunting Prevention - imaru diani; Apriyani Apriyani; Putri Febianti (Masker Medika, 2024)
Introduction: Stunting is a global problem that continues to occur today. The prevalence of stunting worldwide reaches 22.0% or 149.2 million people. Indonesia is one of the countries facing a triple burden in nutritional status with one of the highest stunting incidents in Southeast Asia. It is recorded that the current incidence of stunting in Indonesia has reached 21.6% in 2022, while the target to be achieved is 14% in 2024. According to SDGI data in 2022, the number of stunted toddlers in South Sumatra is 18.6% and Palembang 14.3% of toddlers experience stunting. The causes of stunting are due to lack of nutritional intake in mothers during pregnancy, economic problems, illness in infants, lack of nutritional intake in toddlers, and poor sanitation. Therefore, efforts are needed, one of which starts from the smallest unit in society, namely the family. Efforts to increase family awareness about preventing stunting are through providing education. Objective: to determine the BEGESAH (Various Healthy Community Movement Education) Based on Local Wisdom on Awareness of Stunting Prevention. Method: Quasy experimental study with control group design. The sample was selected by probability sampling with sequential sampling method of 35 people, namely mothers. The intervention group was given a booklet and educational video on stunting prevention, while the control group was not given. The research instrument used a questionnaire on knowledge and attitudes about stunting prevention. Results: Based on data analysis with a paired t-test, both the intervention group and the control group showed a significant p value <0.05. However, when viewed from the significance of the p value, the intervention group has a higher significance than the control group. Conclusion: There is an effect of BEGESAH on family awareness of stunting prevention.